Improving Students' Interest and Learning Outcomes in Short Story Materials by Applying the Concept of Contextual Learning in Class XI DKV SMK Muhammadiyah 4 Kalisat - Rohimah, Ainur; Dzarna, Dzarna; Susetyo, Agus Milu; Fairus, Najma (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study aims to improve students' interest and learning outcomes in short story material through the application of contextual learning models in class XI DKV SMK Muhammadiyah 4 Kalisat. The method used is Classroom Action Research (CAR) which consists of three cycles with stages of planning, implementation, observation, and reflection. The results of the study showed that the application of contextual learning significantly increased student engagement, created a more relevant learning experience, and strengthened their literacy skills. The success of this learning was also influenced by the active role of the teacher as a facilitator who helped students connect the material to real life. In the first cycle, student engagement was still low because the methods used were less interesting and tended to be monotonous. However, in the second cycle, there was an increase in participation even though there were still some obstacles in implementing the learning strategies that had been applied. The third cycle showed more optimal results, with increased motivation, understanding, and students' ability to analyze and appreciate short stories in more depth. The application of a contextual approach not only has a positive impact on student learning outcomes, but also provides a more meaningful and enjoyable learning experience. This finding contributes to the development of literature learning strategies in vocational education, especially in linking materials to the industrial world and students' daily lives. Thus, innovation in learning methods is needed to create a more effective, relevant, and appropriate learning process for students in the modern era.